Stochastic adaptive search for global optimization - Zabinsky Zelda B (Boston Kluwer Academic, 2003)
This book consolidates a collection of papers on the analysis and development of stochastic adaptive search. The first chapter introduces random search algorithms. Chapters2-5 describe the theoretical analysis of a progression of algorithms. Chapter 6 di
Keywords: Global optimization